Roles of Zakat Centre UiTM towards students’ academic development : study in UiTM Shah Alam, Selangor / Nur Syakirah Amirah Ahmad Mohzir - Ahmad Mohzir, Nur Syakirah Amirah (Academy of Contemporary Islamic Studies (ACIS), 2016)
Zakat is an obligatory endowment imposed for those who meet all the criteria prescribed in Islam. People often questioned about the role of zakat centre towards academic development which is sometimes even forgotten by society. The excess zakat grow tremendously from year to year. Arises a few question of the effectiveness of zakat centre distribution towards academic development in UiTM Shah Alam, Selangor at the present time. It is difficult for the zakat centre to manage the number of applications each year. This is because the major problem faced by the agency is the lack of manpower in the collection and distribution of zakat to identify the relevant IPT across the country. Accordingly, the involvement of IPT as agents of distribution and collection of zakat seen among the best alternative to solve this problem. Zakat centre can put the responsibility of collecting and distributing zakat among staff and university students to IPT zakat centre. Indirectly it help zakat centre to identify the recipients throughout the region in their respective states with a more efficient and comprehensive, in addition to optimizing the function and role of zakat centre limited staff. Thus, this paper will discuss the schemes that provided by zakat centre UiTM Shah Alam and how screening is done by the management of zakat in determining which students are eligible to receive aid. Moreover, what the items and packages are available for students who are eligible to receive zakat aid in UiTM Shah Alam. And what are the challenges faced by zakat centre to perform their roles in academic development during carries out tasks as Amil at UiTM. Interviews were been done to central the head unit to answer the question related to UiTM zakat issues and solve the problems faced by the Zakat Central. Hence, the aims of this paper are to discuss in detail about the role of zakat centre UiTM Shah Alam, Selangor to answer some of these issues.